Change in Population Exposure to Future Tropical Cyclones in Northwest Pacific - Lianjie Qin; Xinli Liao; Wei Xu; Chenna Meng; Guangran Zhai (Atmosphere, 2022)
The impact of tropical cyclones is expected to worsen with continued global warming and socioeconomic development. Quantifying population exposure to strong winds and heavy rainfall induced by tropical cyclones is a core element of tropical cyclone population risk assessment. Based on the demographic dataset of Shared Socioeconomic Pathways and future tropical cyclone data, we first calculate and analyze the changes in impact frequency and population exposure to four tropical cyclone scenarios in the Northwest Pacific over the period 2015–2050. Then, we quantitatively assess the contribution rates of climate change, population change, and their joint change to population exposure change. The results show that East China, South China, and Southeast China are the areas with high exposure change. Additionally, most of the high exposure changes (absolute changes over 400,000 people) are significant, and primarily influenced by the changes in local population growth. Overall, exposure change in the Northwest Pacific is mainly influenced by climate change, followed by population change and joint change.